Multicentric carpotarsal osteolysis syndrome with variants of MAFB gene: a case report and literature review - Xianfei Gao; Xiang Fang; Danping Huang; Song Zhang; Huasong Zeng (BMC, 2024)
Abstract Background Multicentric carpotarsal osteolysis (MCTO) is a rare genetic disorder characterized by the progressive loss of bone in the hands, feet, and other skeletal structures. It presents with symptoms that may resemble those of juvenile idiopathic arthritis, making diagnosis challenging for clinicians. The identification of MAF BZIP Transcription Factor B (MAFB) mutations as significant contributors to MCTO represents a major breakthrough in our understanding of the pathogenesis of this rare skeletal disorder. Case presentation Our objective was to present the phenotype, treatment, and outcome of a patient with a variant of MAFB-induced MCTO to broaden the range of clinical features associated with MCTO and share our clinical experience for improved diagnosis and treatment. In our case, early MRI examination of the bones and whole exome sequencing enabled an early and accurate MCTO diagnosis, and timely Denosumab administration resulted in no deterioration. Conclusion This suggests that MRI examination and whole exome sequencing should be considered when MCTO is suspected, and Denosumab might be an option in the treatment of MCTO.